Air-based secondary battery and method for manufacturing the same

JP7917463B2Active Publication Date: 2026-09-08FDK CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023008764
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-01-24
Publication Date
2026-09-08
Estimated Expiration
2043-01-24

AI Technical Summary

Benefits of technology

【0007】 本発明の空気二次電池によれば、充電時に水の電気化学的還元反応で生成した水素原子は、負極板において拡散され、水素吸蔵平衡圧の高い第1領域よりも、空気極から離れて位置する水素吸蔵平衡圧の低い第2領域から先に吸蔵される。このように、充電反応が進みにくい空気極から離れた領域から水素を吸収させることによって、吸蔵されなかった水素原子が水素ガスとして電池の外に抜けてしまうことで容量が低下することを抑制でき、充電受入性の低下を抑制できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007917463000002
    Figure 0007917463000002
  • Figure 0007917463000003
    Figure 0007917463000003
  • Figure 0007917463000004
    Figure 0007917463000004
Patent Text Reader

Abstract

To provide a hydrogen air secondary battery in which reduction of charge acceptability is suppressed, and a manufacturing method thereof.SOLUTION: An air secondary battery 1 comprises an air electrode 40, which contains oxygen in the air as a cathode active material, and an anode 60 which contains a hydrogen-storing alloy as an anode active material. The anode includes a first region 61 opposed with the air electrode and a second region 62 which is positioned separately from the air electrode more than the first region in a thickness direction of the anode. The anode is formed in such a manner that a hydrogen storage equilibrium pressure of the second region becomes lower than a hydrogen storage equilibrium pressure of the first region.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a secondary air battery and a method for manufacturing the same. [Background technology]

[0002] In air batteries, hydrogen-air secondary batteries that use a hydrogen storage alloy as the negative electrode do not require the positive electrode active material to be filled into the battery container, as the positive electrode active material is oxygen from the air. As a result, more negative electrode active material can be filled into the battery container, thus achieving a high energy density. In negative electrodes that use a hydrogen storage alloy as the negative electrode active material, the hydrogen storage alloy is filled into a negative electrode plate made of foamed metal in order to increase the electrical capacity per unit area and to suppress the shedding of powder from the negative electrode core due to hydrogen gas generation. For example, a slurry containing hydrogen storage alloy powder, Ketjenblack, and a binder is filled into nickel foam to produce a negative electrode plate, and after drying, the negative electrode plate is rolled to increase the density of the negative electrode active material within the negative electrode plate before use. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2020-187862 [Overview of the project] [Problems that the invention aims to solve]

[0004] However, increasing the thickness of the negative electrode plate to increase electrical capacity makes it easier for hydrogen gas to be generated as a side reaction during charging of hydrogen-air secondary batteries, thus reducing charge acceptance. These factors lead to a decrease in battery capacity, deterioration due to expansion or powder shedding of the negative electrode plate, and a shortened charge-discharge cycle life. In addition, thicker negative electrode plates have a larger bending radius, which also affects battery manufacturing.

[0005] Therefore, the object of the present invention is to provide a hydrogen-air secondary battery and a method for manufacturing the same in which a decrease in charge acceptance is suppressed throughout the entire region of the negative electrode, regardless of its thickness. [Means for solving the problem]

[0006] To achieve the above objective, the air secondary battery of the present invention comprises an air electrode using oxygen from the air as the positive electrode active material, and a negative electrode containing a hydrogen storage alloy as the negative electrode active material, wherein the negative electrode has a first region facing the air electrode and a second region located further away from the air electrode than the first region in the thickness direction of the negative electrode, and the hydrogen storage equilibrium pressure of the second region is lower than the hydrogen storage equilibrium pressure of the first region. [Effects of the Invention]

[0007] In the air-based secondary battery of the present invention, hydrogen atoms generated by the electrochemical reduction reaction of water during charging are diffused on the negative electrode plate and are absorbed first in the second region, which is located further from the air electrode and has a lower hydrogen absorption equilibrium pressure, rather than in the first region, which has a higher hydrogen absorption equilibrium pressure. By absorbing hydrogen from the region further from the air electrode, where the charging reaction is less likely to proceed, it is possible to suppress the decrease in capacity caused by unabsorbed hydrogen atoms escaping from the battery as hydrogen gas, and thus suppress the decrease in charge acceptance. [Brief explanation of the drawing]

[0008] [Figure 1] This is a cross-sectional view showing an air-based secondary battery according to this embodiment. [Figure 2] Figure 1 is a cross-sectional view of the electrode group of the air-based secondary battery shown. [Figure 3] (a) is a graph showing the PCT characteristic curve of hydrogen storage alloy A, and (b) is a graph showing the PCT characteristic curve of hydrogen storage alloy B. [Figure 4] This is a flowchart showing the manufacturing process for the negative electrode of a rechargeable air battery. [Figure 5] This is a cross-sectional view showing an air-based secondary battery according to the second embodiment. [Modes for carrying out the invention]

[0009] Hereinafter, the hydrogen-air secondary battery (hereinafter sometimes referred to as "battery") according to this embodiment will be described with reference to the drawings. 1. Configuration of a hydrogen-air secondary battery Figure 1 shows a cross-sectional view of a hydrogen-air secondary battery according to the first embodiment. The hydrogen-air secondary battery 1 consists of air secondary battery cells and is housed in a battery case 10. In the battery case 10, a flow channel plate 20, a water-repellent film 30, an air electrode (positive electrode) 40, a separator 50, and a negative electrode 60 are arranged in order from the positive electrode side to the negative electrode side. The air electrode 40 faces the negative electrode 60 via the separator 50.

[0010] The flow channel plate 20 is made of a rectangular flat plate that exhibits conductivity, and on one main surface 21 facing the air electrode 40, there is a ventilation passage 22 through which air reacting with the air electrode 40 flows in the in-plane direction, an introduction passage 23 for introducing air from the outside into the ventilation passage 22, and an outlet passage 24 for leading the air that has flowed through the ventilation passage 22 to the outside. The introduction passage 23 and the outlet passage 24 each function as flow channels and penetrate the flow channel plate 20 in the thickness direction.

[0011] Furthermore, the water-repellent film 30 is fixed to the main surface 21 of the flow channel plate 20 via a gas diffusion film 31 by a rectangular frame 32. The water-repellent film 30 is fixed to the flow channel plate 20 while blocking the opening on the main surface 21 of the ventilation passage 22, without covering the inlet passage 23 and outlet passage 24.

[0012] The ventilation passage 22 is formed as a groove on the main surface 21 of the flow channel plate 20, extending from one end to the other end in the direction through which air passes, and its plan view shape is a single serpentine shape. The ventilation passage 22 supplies oxygen from the air to the air electrode 40 during discharge and discharges oxygen generated from the air electrode 40 to the outside during charging. The ventilation passage 22 opens toward the air electrode 40, and its cross-section in the direction intersecting the direction of air passage is formed into an appropriate shape such as a rectangle.

[0013] The gas diffusion membrane 31 is formed of, for example, a porous substrate, and has a function of efficiently diffusing air and hydrogen required for the charge-discharge reaction of the air electrode 40.

[0014] The water-repellent membrane 30 is a liquid-tight gas-permeable membrane formed of a microporous resin film. It allows air flowing through the vent path 22 to pass to the air electrode 40, and prevents the electrolyte present on the air electrode 40 side from leaking into the vent path 22. The water-repellent membrane 30 has a shape and size that blocks the entire length of the opening of the vent path 22 from one end to the other end along the flow direction of the air flow, but does not block the introduction path 23 and the discharge path 24.

[0015] The frame body 32 is formed into a rectangular shape from a conductive material, and a frame surface 34 facing the water-repellent membrane 30 is flat. The frame body 32 fixes the water-repellent membrane 30 to the flow path plate 20, and surrounds the air electrode 40 inside the frame body 32.

[0016] The air electrode 40 is composed of a conductive air electrode core body having a large number of pores, and an air electrode mixture (positive electrode mixture) held in the pores and on the surface of the air electrode core body. The air electrode mixture includes a redox catalyst, a conductive agent, and a fluororesin. The redox catalyst is not particularly limited as long as it has a dual function of redox. As the redox catalyst, it is preferable to use a pyrochlore-type bismuth ruthenium oxide. The production of the air electrode 40 will be described later.

[0017] The separator 50 is disposed between the air electrode 40 and the negative electrode 60, and electrically insulates the air electrode 40 and the negative electrode 60 from each other. The separator 50 is made of, for example, a nonwoven fabric of polyamide fibers or a nonwoven fabric of polyolefin fibers, and contains an alkaline electrolyte such as a KOH solution therein. In the present embodiment, the separator 50 has a rectangular shape as a whole, and its planar shape is formed larger than the planar shape of the air electrode 40 and the planar shape of the negative electrode 60.

[0018] As shown in Figure 2, the negative electrode 60 consists of a proximal negative electrode plate 61 facing the air electrode 40 and a distal negative electrode plate 62 located further from the air electrode 40 than the proximal negative electrode plate. The proximal negative electrode plate 61 and the distal negative electrode plate 62 are superimposed in the thickness direction of the negative electrode 60. The proximal negative electrode plate 61 and the distal negative electrode plate 62 each consist of a conductive negative electrode core having numerous voids and a negative electrode mixture held in the voids and on the surface of the negative electrode core. For example, foamed nickel is used as the negative electrode core. The negative electrode mixture includes hydrogen storage alloy powder as a negative electrode active material, a conductive agent, and a binder. The hydrogen storage alloy powder used in the proximal negative electrode plate 61 and the distal negative electrode plate 62 has a different composition. The distal negative electrode plate 62 is filled with hydrogen storage alloy powder that has a lower hydrogen storage equilibrium pressure than the hydrogen storage alloy powder filled in the proximal negative electrode plate 61. Graphite, carbon black, and the like can be used as conductive agents. The fabrication of the negative electrode 60 will be described later. The proximal negative electrode plate 61 is an example of the first region or first negative electrode plate, and the distal negative electrode plate 62 is an example of the second region or second negative electrode plate.

[0019] The air electrode 40, separator 50, and negative electrode 60 constitute the electrode group 100 and are positioned between the air electrode opposing wall 16 and the negative electrode opposing wall 26 of the battery case 10. The edge of the separator 50 is sandwiched and fixed in place by the side wall between the air electrode opposing wall 16 and the negative electrode opposing wall 26.

[0020] 2. Manufacturing of hydrogen-air rechargeable batteries The manufacturing process for hydrogen-air secondary battery 1 is described below.

[0021] (1) Fabrication of the air electrode First, the manufacturing process of the air electrode mixture will be described. Bi(NO3)3·5H2O and RuCl3·3H2O were added to a dilute nitric acid aqueous solution at 75°C in a molar concentration ratio of 0.75:1.00, and stirred to prepare a mixed aqueous solution of Bi(NO3)3·5H2O and RuCl3·3H2O. A 2 mol / L NaOH aqueous solution was added to this mixed aqueous solution, and the mixture was stirred while maintaining a temperature of 75°C and oxygen bubbling. The precipitate produced by this operation was collected by suction filtration and dried to obtain a precursor powder. The precursor powder was heat-treated by heating to 540°C in an air atmosphere and holding for 3 hours to obtain a calcined product. By-products were removed from the calcined product by suction filtration in the following order: distilled water at 75°C, 2 mol / L nitric acid aqueous solution, and distilled water at 75°C. The calcined product collected by suction filtration was heated to 120°C and dried to obtain a bismuth ruthenium oxide catalyst (pyrochlore-type composite oxide catalyst) for hydrogen-air secondary batteries. The primary particle size observed by SEM was 10–50 nm.

[0022] Bismuth ruthenium oxide catalyst was pulverized using a wet bead mill (Ashizawa Finetech, Labstar Mini, DMS65). Ion-exchanged water was added to achieve a solid content ratio of 20 wt% per unit weight of the bismuth ruthenium oxide catalyst, and then 2 wt% of a dispersant (Sunopco, SN Dispersant 5468) relative to the catalyst weight was added to prepare a catalyst dispersion. This catalyst dispersion was pumped into the bead mill at a predetermined flow rate and pulverized with zirconia beads (bead diameter 0.1 mm) at a peripheral speed of 8 m / s. The discharged processed liquid was then pumped back into the apparatus, and the pulverization and discharge process was repeated a total of 5 times (5 passes) to obtain a dispersion with a bismuth ruthenium oxide concentration of 20 wt.%.

[0023] This dispersion was weighed to 50 parts by mass based on the weight of bismuth ruthenium oxide. To this, 30 parts by mass of high-purity natural graphite (SEC Carbon Co., Ltd., SNO-1T, average particle size 1-2 μm) was added as a carbon material, 30 parts by mass of FEP dispersion (Mitsui Chemours Fluoroproducts Co., Ltd., perfluoroethylene propene copolymer, 120-JRB, average particle size 0.2 μm) was added as a fluororesin in terms of solid content ratio, and 1 part by mass of hydroxypropyl cellulose (HPC) was added as a viscosity modifier. Deionized water was then added to further adjust the viscosity. At this time, the total water content of the slurry was the sum of the added deionized water, the deionized water contained in the dispersion, and the water content contained in the FEP dispersion. That is, the total was 385 parts by mass.

[0024] These were mixed and stirred in a rotation-orbit mixer to obtain a slurry for use as an air electrode additive. The weight ratio of solids in the slurry, excluding the water content in the deionized water and FEP dispersion, was 21.4% of the total slurry weight. The weight ratios of bismuth ruthenium oxide, graphite, fluororesin, HPC, and dispersant contained in the solids were 44.9%, 26.9%, 26.9%, 0.9%, and 0.4%, respectively.

[0025] Sheet-type foamed nickel (thickness 1.6 mm, average pore size 580 μm, basis weight 575 g / m²) 2 The foamed nickel core was roll-rolled to a thickness of 0.45 mm to form an air electrode core. The slurry described above was filled into this air electrode core. The slurry-filled air electrode core was then dried at 60°C for 1 hour, rolled to 0.25 mm, and cut to an electrode area of ​​40 mm x 40 mm. The cut electrodes were fired in an electric furnace at 250°C for 13 minutes while flowing nitrogen gas at a flow rate of 1 L / min to obtain air electrode 40. The weight of the air electrode mixture (slurry) filled into the air electrode core was calculated from the difference between the weight of the obtained air electrode 40 and the weight of the foamed nickel core. Furthermore, the amount of bismuth ruthenium oxide catalyst per unit area was determined from the weight ratio of the added air electrode mixture. As a result, the amount of catalyst in this air electrode 40 was 7.5 mg / cm³. 2was obtained.

[0026] (2) Fabrication of negative electrode The production of hydrogen storage alloy powder A filled into the proximal negative electrode plate 61 and hydrogen storage alloy powder B filled into the distal negative electrode plate 62 will be described.

[0027] (2-1) Fabrication of hydrogen storage alloy A After mixing respective metallic materials of La, Nd, Mg, Ni, Al and Cr, the mixture is charged into a high-frequency induction melting furnace and melted under an argon gas atmosphere. The obtained molten metal is poured into a mold and cooled to room temperature of 25°C to produce an ingot. Note that the hydrogen storage equilibrium pressure is adjusted by the composition of the respective metallic materials described above. A suitable hydrogen storage equilibrium pressure for use as a negative electrode of a hydrogen-air secondary battery is 0.04 to 0.2 MPa under the present test condition of H / M = 0.4. When the hydrogen storage equilibrium pressure is lower than the above value, there are problems that the battery voltage drops excessively and the capacity decreases. Conversely, when the hydrogen storage equilibrium pressure is higher than the above value, there is a problem that charge acceptance is degraded due to generation of hydrogen gas.

[0028] After this ingot was held for 10 hours in an argon gas atmosphere at a temperature of 1000°C, it was cooled to room temperature of 25°C. The cooled ingot was mechanically pulverized under an argon gas atmosphere to obtain a rare earth-Mg-Ni-based hydrogen storage alloy powder. When the volume average particle diameter (MV) of the obtained rare earth-Mg-Ni-based hydrogen storage alloy powder was measured by a laser diffraction / scattering particle size distribution analyzer, the volume average particle diameter (MV) of the rare earth-Mg-Ni-based hydrogen storage alloy powder was 35 μm.

[0029] When the composition of this hydrogen storage alloy powder was analyzed by high-frequency plasma spectroscopy (ICP), the composition was: (La 0.1 Nd 0.9 ) 0.91 Mg 0.09 Ni 3.52 Al 0.17 Cr 0.01 was obtained.

[0030] The obtained hydrogen storage alloy was hydrogenated at 80°C using a PCT hydrogenation characteristics evaluation device until the maximum hydrogen pressure reached 1 MPa, and then dehydrogenated to activate it. The PCT characteristic curve of hydrogen storage alloy A measured up to the maximum hydrogen pressure of 1 MPa at 80°C is shown in Figure 3(a). In Figure 3(a), H / M represents the number of hydrogen atoms (H) per metal atom (M). At H / M = 0.4, the hydrogen storage equilibrium pressure was 0.20 MPa and the release pressure was 0.15 MPa.

[0031] To measure the electrochemical capacity of the above-mentioned hydrogen storage alloy A, the following battery was experimentally constructed. 0.25 g of hydrogen storage alloy powder and 0.75 g of nickel powder were mixed and molded to create a 10 mmφ pellet electrode as the negative electrode. 100 mL of 8 mol / L KOH aqueous solution was placed in a cylindrical container, with the pellet electrode and mercury oxide reference electrode inserted in the center. A nickel hydroxide counter electrode with a capacity sufficiently larger than the negative electrode was placed at the edge of the container. Using this negative electrode capacity-restricted battery, a charge-discharge test was performed, where the negative electrode capacity was calculated assuming an alloy capacity of 300 mAh / g (1 It), and charged for 0.5 It × 200 minutes, then discharged at 0.5 It to a negative electrode potential of -0.3 V relative to the mercury oxide reference electrode. The electrochemical capacity was then determined. The obtained electrochemical capacity was 353 mAh / g.

[0032] (2-2) Preparation of hydrogen storage alloy B As alloy B, a powder of a rare-earth-Mg-Ni-based hydrogen storage alloy was obtained using the same method as for hydrogen storage alloy A. Its composition was (La 0.2 Nd 0.8 ) 0.89 Mg 0.11 Ni 3.42 Al 0.17 Cr 0.01 The obtained hydrogen storage alloy B was activated using a PCT hydrogenation characteristics evaluation apparatus under the same conditions as hydrogen storage alloy A, and the PCT characteristic curve measured up to a maximum hydrogen pressure of 1 MPa at a temperature of 80°C is shown in Figure 3(b). Referring to Figure 3(b), the hydrogen storage equilibrium pressure at H / M=0.4 was 0.13 MPa and the release pressure was 0.08 MPa. The electrochemical capacity was 357 mAh / g.

[0033] (2-3) Fabrication of the negative electrode To hydrogen storage alloy A, 100 parts by weight of the obtained powder was mixed with 0.2 parts by weight of sodium polyacrylate, 0.04 parts by weight of carboxymethylcellulose, 0.3 parts by weight of carbon black, and 22.4 parts by weight of water to prepare a negative electrode mixture paste.

[0034] This paste was filled into a sheet of nickel foam to serve as the negative electrode core. The nickel foam had a thickness of 1.7 mm and a basis weight of 300 g / m2. The negative electrode core filled with the negative electrode mixture was dried and roll-rolled to increase the amount of hydrogen storage alloy per unit volume. Then, it was cut into 40 mm x 40 mm pieces to obtain an alloy A negative electrode plate (Figure 4, step S1). Hydrogen storage alloy B was filled into the negative electrode core in the same manner as hydrogen storage alloy A, and after drying, roll-rolling, and cutting, an alloy B negative electrode plate was obtained (step S2). In this embodiment, the amount of negative electrode mixture filled into the negative electrode core was adjusted so that both the alloy A negative electrode plate and the alloy B negative electrode plate had an electrical capacity of 2500 mAh.

[0035] (3) Fabrication of a secondary air battery A negative electrode 60 was fabricated by bringing an alloy A negative electrode plate and an alloy B negative electrode plate into contact with each other in the direction of film thickness (Step S3). Next, the negative electrode 60, a separator 50 made of nonwoven fabric, an air electrode 40, a PTFE microporous membrane (45 mm × 45 mm, thickness 0.1 mm) as a water-repellent film 30, and a nonwoven diffusion paper (40 mm × 40 mm, thickness 0.2 mm, not shown) were stacked and placed inside the battery case 10, and a flow channel plate 20 having a ventilation passage 22 (serpentine structure with a cross-section of 1 mm × 1 mm) was attached. Inside the battery case 10, the alloy A negative electrode plate of the negative electrode 60 was positioned as the proximal negative electrode plate 61 facing the air electrode, and the alloy B negative electrode plate was positioned as the distal negative electrode plate 62 at a greater distance from the air electrode than the proximal negative electrode plate 61 (Step S4). Then, a 5 mol / L KOH aqueous solution was poured into the battery case 10. During both charging and discharging of the battery, air was guided from the inlet passage 23 to the vent passage 22 and discharged from the outlet passage 24, with a constant supply of 50 mL / min of air to the vent passage 22.

[0036] The hydrogen-air secondary battery 1 is manufactured through the process described above.

[0037] (Example 1) The hydrogen-air secondary battery manufactured by the above process is referred to as Example 1. Specifically, in the battery of Example 1, the proximal negative electrode plate 61 contains alloy powder A with a high water storage equilibrium pressure, and the distal negative electrode plate 62 contains alloy powder B with a low water storage equilibrium pressure.

[0038] (Comparative Example 1) In the same hydrogen-air secondary battery as in Example 1, instead of the negative electrode 60 of Example 1, the negative electrode was fabricated by stacking alloy B negative electrode plates for both the proximal negative electrode plate 61 and the distal negative electrode plate 62.

[0039] (Comparative Example 2) In the same hydrogen-air secondary battery as in Example 1, instead of the negative electrode 60 of Example 1, the negative electrode was fabricated by stacking alloy A negative electrode plates for both the proximal negative electrode plate 61 and the distal negative electrode plate 62.

[0040] (Comparative Example 3) In the same hydrogen-air secondary battery as in Example 1, a negative electrode was fabricated by stacking an alloy B negative electrode plate as the proximal negative electrode plate 61 and an alloy A negative electrode plate as the distal negative electrode plate 62. That is, one side of the negative electrode plate facing the air electrode 40 was filled with alloy B powder, which has a low hydrogen storage equilibrium pressure, and the other side located away from the air electrode 40 was filled with alloy A powder, which has a high hydrogen storage equilibrium pressure. 3. Evaluation of battery characteristics

[0041] (3-1) Evaluation Method Each hydrogen-air secondary battery of Example 1 and Comparative Examples 1-3 was aged at 60°C for 12 hours, and then cooled to room temperature. Then, 4000mAh, which corresponds to 80% of the negative electrode design capacity, was defined as 1It, and a cycle of charging 0.05It for 20 hours and discharging 0.05It (discharge termination voltage EV = 0.4V) was repeatedly performed, and the discharge capacity after the third cycle was determined. The Ah capacity efficiency was calculated by dividing this discharge capacity by the charging capacity of 4000mAh (80% of the negative electrode design capacity).

[0042] (3-2) Results Table 1 shows the negative electrode configuration and battery characteristics results for Example 1 and Comparative Examples 1-3.

[0043] [Table 1]

[0044] The discharge capacities were 3974mAh for Example 1, 3957mAh for Comparative Example 1, 3934mAh for Comparative Example 2, and 3915mAh for Comparative Example 3, with the hydrogen-air secondary battery of Example 1 achieving the highest battery capacity. Comparing the battery capacities of each battery, the following two points can be observed. First, when two negative electrode plates made of the same alloy are stacked to form the negative electrode (Comparative Examples 1 and 2), the hydrogen-air secondary battery in which negative electrode 60 is made of hydrogen storage alloy B, which has a lower equilibrium pressure, has a higher discharge capacity. Second, when negative electrode plates made of two different types of alloys are stacked to form the negative electrode (Example and Comparative Example 3), changing the order in which the plates are stacked results in a smaller battery capacity than when two negative electrode plates of the same alloy are stacked to form the negative electrode. In other words, it can be seen that not only the magnitude of the hydrogen storage equilibrium pressure but also the distance of each negative electrode plate from the positive electrode has an effect.

[0045] When using only one type of alloy for the negative electrode, a lower hydrogen storage equilibrium pressure of the alloy results in a greater potential difference between the charging reaction (where hydrogen atoms are generated and stored in the alloy) and the side reaction (where hydrogen gas is generated). This allows the charging reaction to proceed preferentially, leading to higher capacity efficiency. However, lowering the hydrogen storage equilibrium pressure of the alloy too much can reduce the voltage (output) during discharge.

[0046] On the other hand, as in Example 1, an even higher discharge capacity was obtained by constructing the negative electrode by combining a negative electrode plate made of an alloy with a low hydrogen storage equilibrium pressure and a negative electrode plate made of an alloy with a high hydrogen storage equilibrium pressure. Specifically, by using alloy A, which has a higher hydrogen storage equilibrium pressure than alloy B, as the negative electrode compound for the proximal negative electrode plate closer to the air electrode, and alloy B, which has a lower hydrogen storage equilibrium pressure than alloy A, for the distal negative electrode plate further from the air electrode than the proximal negative electrode plate, the hydrogen generated by the side reaction during charging of the hydrogen-air secondary battery can be absorbed at the negative electrode from a part with high ion diffusion resistance where the charging reaction is difficult to proceed and which is far from the air electrode. Therefore, the entire negative electrode can be used efficiently for hydrogen storage.

[0047] In contrast, in Comparative Example 3, the hydrogen storage equilibrium pressure of alloy B in the proximal negative electrode plate 61 is lower than that of alloy A in the distal negative electrode plate 62. Therefore, hydrogen absorption begins first in alloy B of the proximal negative electrode plate 61. Consequently, the distal negative electrode plate, which is further away from the air electrode than the proximal negative electrode plate, has a higher ion diffusion resistance and a higher hydrogen storage equilibrium pressure, making it less likely to absorb hydrogen. As a result, Comparative Example 3 is more prone to the generation of hydrogen gas as a side reaction, and its discharge capacity is lower compared to the Examples and Comparative Examples 1 and 2.

[0048] Furthermore, the Ah capacity efficiency was 99.4% for Example 1, 98.9% for Comparative Example 1, 98.3% for Comparative Example 2, and 97.8% for Comparative Example 3, with Example 1 having the highest Ah capacity efficiency.

[0049] As described above, in the negative electrode, an alloy with a high hydrogen storage equilibrium pressure is used as the hydrogen storage alloy filling the region close to the air electrode, i.e., the surface facing the air electrode, and an alloy with a low hydrogen storage equilibrium pressure is used to fill the region away from the air electrode along the thickness direction of the negative electrode from the opposing surface. This allows for efficient absorption of hydrogen generated during charging using the entire negative electrode, thereby suppressing the decrease in capacity efficiency due to side reactions and increasing the discharge capacity of the hydrogen-air secondary battery.

[0050] Furthermore, when the negative electrode is thick, the charging reaction is less likely to proceed at the distal negative electrode plate, which is farther from the air electrode, due to its high ion diffusion resistance. However, the distal negative electrode plate at the negative electrode has a lower hydrogen equilibrium pressure for alloy B, allowing it to absorb hydrogen before the proximal negative electrode plate (alloy A). Therefore, the thickness of the negative electrode can be used effectively.

[0051] In the above embodiment, the negative electrode was made by stacking two negative electrode plates. However, similar effects can be achieved by, for example, die-coating a single negative electrode core in which one side facing the air electrode is filled with alloy A, which has a high hydrogen storage equilibrium pressure, and the other side facing the opposite direction in the thickness direction is filled with alloy B, which has a lower hydrogen storage equilibrium pressure than alloy A.

[0052] Next, the hydrogen-air secondary battery 1' of the second embodiment will be described below with reference to Figure 5. The electrode group 100' housed in the battery case 10' is arranged in the order of first air electrode 40A, negative electrode 60', and second air electrode 40B in direction A. Air electrode 40A faces the negative electrode 60' via separator 50A. Air electrode 40B faces the negative electrode 60' from the opposite side of air electrode 40A via separator 50B. In other words, the air secondary battery shown in Figure 6 is considered equivalent to a configuration in which two battery cells sharing a negative electrode 60' are electrically connected in parallel. Therefore, only the negative electrode 60' will be described below.

[0053] The negative electrode 60' consists of three negative electrode plates stacked on top of each other in the thickness direction: a first proximal negative electrode plate 61A facing the first air electrode 40, a second proximal negative electrode plate 61B facing the second air electrode 40, and an intermediate negative electrode plate 62' positioned between the first and second proximal negative electrode plates 61A and 61B. Each negative electrode plate 61A, 61B, and 62' consists of a conductive negative electrode core having numerous voids and a negative electrode mixture held within the voids and on the surface of the negative electrode core. Similar to the embodiment shown in Figure 1, the first and second proximal negative electrode plates 61A and 61B are made using alloy A powder with a high hydrogen storage equilibrium pressure. On the other hand, the intermediate negative electrode plate 62' is made using alloy B powder with a low hydrogen storage equilibrium pressure. After the fabrication of the individual negative electrode plates 61A, 61B, and 62', the first proximal negative electrode plate 61A, the intermediate negative electrode plate 62', and the second proximal negative electrode plate 61B are stacked in that order, and the negative electrode 60' is fabricated by roll rolling. The second proximal negative electrode plate 61B is an example of a third region.

[0054] Then, an electrode group 100' is fabricated such that the first air electrode plate 40A faces the first proximal negative electrode plate 61A which is superimposed via an intermediate negative electrode plate 62', and the second air electrode plate faces the second proximal negative electrode plate 61B. The electrode group 100' is then housed in a battery case 10' to fabricate a hydrogen-air secondary battery 1'.

[0055] In the battery of this embodiment, the charging reaction is slow to proceed due to the problem of ion diffusion resistance, and the hydrogen storage equilibrium pressure of the alloy in the central part of the thickness direction of the negative electrode, which is farther from the air electrode, is low. As a result, hydrogen is absorbed sequentially from the central part in the thickness direction of the negative electrode. Therefore, the entire region of the negative electrode can be used efficiently for hydrogen storage. [Explanation of Symbols]

[0056] 1. Air-based rechargeable battery 10 Battery Case 40 Air pole 60 negative electrode 61 1st area 62 Second area

Claims

1. An air electrode using oxygen from the air as the positive electrode active material, A negative electrode containing a hydrogen storage alloy as the negative electrode active material, A secondary air battery equipped with, The negative electrode has a first region facing the air electrode and a second region located further away from the air electrode than the first region in the thickness direction of the negative electrode. A secondary air battery characterized in that the hydrogen storage equilibrium pressure in the second region is lower than the hydrogen storage equilibrium pressure in the first region.

2. The negative electrode has a proximal negative electrode plate and a distal negative electrode plate stacked in the thickness direction. The air secondary battery according to claim 1, wherein the proximal negative electrode plate includes the first region and the distal negative electrode plate includes the second region.

3. Furthermore, the negative electrode has a second air electrode, which is separate from the air electrode, on the opposite side of the air electrode. The negative electrode further has a third region facing the second air electrode, on the opposite side of the second region from the first region in the thickness direction of the negative electrode. The air secondary battery according to claim 1, wherein the hydrogen storage equilibrium pressure in the third region is equal to the hydrogen storage equilibrium pressure in the first region.

4. A method for manufacturing a secondary air battery, A step of forming a first negative electrode plate containing a first hydrogen storage alloy, A step of forming a second negative electrode plate containing a second hydrogen storage alloy, A step of forming a negative electrode by stacking the first negative electrode plate on the second negative electrode plate, A step of manufacturing an electrode group by arranging the negative electrodes such that the first negative electrode plate is closer to the air electrode than the second negative electrode plate, Includes, A method characterized in that the hydrogen storage equilibrium pressure of the second negative electrode plate is lower than the hydrogen storage equilibrium pressure of the first negative electrode plate.

Citation Information

Patent Citations

  • Hydrogen absorption electrode

    JP1985212958A

  • Hydrogen storage alloy electrode for alkaline storage battery

    JP1990227958A

  • Hydrogen storage alloy electrode for alkaline storage battery

    JP2000268815A

  • Hydrogen / air secondary battery

    JP2012064477A

  • Metal air battery

    JP2015022871A